The mediating role of green training to the influence of green organizational culture to green organizational citizenship behavior and green employee involvement - Lanatri Danirmala; Wisnu Prajogo (Program Studi S3 Ilmu Manajemen, 2022)
At present, concern for the environment is being intensified by companies around the world. Employees in the organization are taught and provided with knowledge, learning, and real practice to care for the environment. Companies must have a competitive advantage to differentiate them from other companies. One way is to apply environmental care. In order to implement these goals, the company applies various ways to achieve them. Green Human Resource Management (GHRM) is an environmental management practice that is supported by human resources, because it can stimulate organizational success. This research used online survey on 211 respondents. Validity and reliability were tested by factor analysis using SPSS 15.0 software which stated that all items were valid and reliable. The hypothesis was tested using WarpPLS 7.0 software. All hypotheses are supported, green organizational culture has a positive and significant effect on green training, green training has a positive and significant effect on organizational citizenship behavior environment, green training has a positive and significant effect on green employee involvement, there is an indirect effect on organizational citizenship behavior environment and green employee involvement mediated by green training.